Combined Gravimetric–Seismic Crustal Model for Antarctica - Baranov, Alexey; Tenzer, Robert; Bagherbandi, Mohammad (Surveys in Geophysics, 2017)
The latest seismic data and improved information about the subglacial bedrock relief are used in this study to estimate the sediment and crustal thickness under the Antarctic continent. Since large parts of Antarctica are not yet covered by seismic surveys, the gravity and crustal structure models are used to interpolate the Moho information where seismic data are missing. The gravity information is also extended offshore to detect the Moho under continental margins and neighboring oceanic crust. The processing strategy involves the solution to the Vening Meinesz-Moritz's inverse problem of isostasy constrained on seismic data. A comparison of our new results with existing studies indicates a substantial improvement in the sediment and crustal models. The seismic data analysis shows significant sediment accumulations in Antarctica, with broad sedimentary basins. According to our result, the maximum sediment thickness in Antarctica is about 15 km under Filchner-Ronne Ice Shelf. The Moho relief closely resembles major geological and tectonic features. A rather thick continental crust of East Antarctic Craton is separated from a complex geological/tectonic structure of West Antarctica by the Transantarctic Mountains. The average Moho depth of 34.1 km under the Antarctic continent slightly differs from previous estimates. A maximum Moho deepening of 58.2 km under the Gamburtsev Subglacial Mountains in East Antarctica confirmed the presence of deep and compact orogenic roots. Another large Moho depth in East Antarctica is detected under Dronning Maud Land with two orogenic roots under Wohlthat Massif (48–50 km) and the Kottas Mountains (48–50 km) that are separated by a relatively thin crust along Jutulstraumen Rift. The Moho depth under central parts of the Transantarctic Mountains reaches 46 km. The maximum Moho deepening (34–38 km) in West Antarctica is under the Antarctic Peninsula. The Moho depth minima in East Antarctica are found under the Lambert Trench (24–28 km), while in West Antarctica the Moho depth ...